Diffuse X-ray Scattering from NaCl - K. Basar; Xianglian Xianglian; T. Sakuma (Institut Teknologi Bandung, 2006)
The diffuse X-ray scattering intensities from ionic crystal NaCl at 22 K and 290 K have been measured using Cu-Kα radiation. The temperature dependence of the oscillatory diffuse scattering has been observed. The oscillatory diffuse scattering from NaCl is explained by the correlation effect between the thermal displacements of atoms up to 2nd nearest neighboring atoms in the crystal of NaCl.